Perlindungan Hukum bagi Konsumen Terkait Klausula Baku dalam Fidusia terhadap Perampasan Kendaraan Bermotor Dijalan Raya Oleh Debt Collector Kota Sukabumi - Rizky Maulana Yusuf; Temmy Fitriah Alfiani; Prahasti Suyaman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Regulations stipulating that every consumer’s rights and protections must be safeguarded, as well as consumer protection in general, have received significant attention; this is because consumers should be protected from various forms of transactional fraud, granted the right to clear information, and, of course, guaranteed the right to be free from discrimination and to ensure their safety. This is the basis for this study, which aims to identify standard clauses in (Fiduciary) regarding the repossession of vehicles on public roads in light of Law No. 8 of 1999 on Consumer Protection, as well as to determine how legal protection for consumers against the repossession of motor vehicles on public roads by debt collectors in the city of Sukabumi relates to Law No. 42 of 1999 on Fiduciary Security. In this study, the method employed is a normative legal method, and the problem-solving approach used in this paper is the case approach. The results of the study indicate that motor vehicle financing agreements entered into by leasing companies are not in line with the provisions of the Consumer Protection Law, and that such agreements, which favor the business operators, clearly violate the Consumer Protection Law in current practice. Furthermore, if the repossession of a vehicle by a financing institution (leasing company) through a debt collection agency is not accompanied by a certificate of security interest, it may be considered a civil tort.